2015
DOI: 10.1177/2050312115612803
|View full text |Cite
|
Sign up to set email alerts
|

Single high dose gentamicin for perioperative prophylaxis in orthopedic surgery: Evaluation of nephrotoxicity

Abstract: Background:Recent studies described an increase in acute kidney injury when high dose gentamicin was included in perioperative prophylaxis for orthopedic surgeries. To this effect, we compared the rate of nephrotoxicity for selected orthopedic surgeries where gentamicin was included (Gentamicin Group) to those where it was not included (Control Group) for perioperative prophylaxis and evaluated risk factors for nephrotoxicity.Methods:Spine, hip and knee surgeries performed between April 2011 and December 2013 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…Thirty‐six studies were included in the final synthesis: one thesis and 35 journal articles . The 36 studies included 11 randomized controlled studies (two crossover designs), 18 cohort studies, one retrospective survey, three pharmacokinetic and three quasiexperimental studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Thirty‐six studies were included in the final synthesis: one thesis and 35 journal articles . The 36 studies included 11 randomized controlled studies (two crossover designs), 18 cohort studies, one retrospective survey, three pharmacokinetic and three quasiexperimental studies.…”
Section: Resultsmentioning
confidence: 99%
“…Reported adverse events are summarized in Table . Twenty‐three , of the 36 included studies, reported adverse events in the gentamicin arm of their study although not all adverse events were related to gentamicin. Pons et al .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations